2021
DOI: 10.1002/aqc.3591
|View full text |Cite
|
Sign up to set email alerts
|

Improved detection sensitivity using an optimal eDNA preservation and extraction workflow and its application to threatened sawfishes

Abstract: 1. Pressures on coastal ecosystems are increasing and aquatic species that are restricted to these habitats are facing the threat of extinction. However, the true extent of many threatened and rare aquatic species, especially elasmobranchs, remains unclear due to high levels of data deficiency and poor efficacy of traditional survey methods. Sawfishes (Pristidae), a family of shark-like rays, are among

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 97 publications
1
22
0
Order By: Relevance
“…There is little information available on the relative decay rates of different genes, although some eDNA studies have shown that the frequencies of positives can differ depending on the target locus (Zhan et al, 2014; Wood et al, 2019). Primers were recently published to target a small fragment of the 12S ribosomal RNA ( 12S ) locus in P. pectinata (Cooper et al, 2021), although additional cross‐testing in closely related, co‐occurring species (e.g. guitarfish) is needed before this assay can be incorporated into eDNA surveys in the Atlantic Ocean.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is little information available on the relative decay rates of different genes, although some eDNA studies have shown that the frequencies of positives can differ depending on the target locus (Zhan et al, 2014; Wood et al, 2019). Primers were recently published to target a small fragment of the 12S ribosomal RNA ( 12S ) locus in P. pectinata (Cooper et al, 2021), although additional cross‐testing in closely related, co‐occurring species (e.g. guitarfish) is needed before this assay can be incorporated into eDNA surveys in the Atlantic Ocean.…”
Section: Discussionmentioning
confidence: 99%
“…ddPCR™ assays offer greater sensitivity (Baker et al, 2018; Lehman et al, 2020; Drymon et al, 2021) and more precise quantification of target DNA when compared to conventional PCR (e.g. Simpfendorfer et al, 2016; Bonfil et al, 2021) or quantitative PCR approaches (see Wood et al, 2019; Cooper et al, 2021), making them ideal for ‘early detection’ surveys targeting highly threatened species.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of filtration, where it is recommended to maximize collection of trace eDNA through use of a small pore size (Minamoto et al, 2015;Turner et al, 2014) or increase filtrate volume (Sepulveda et al, 2019), highly turbid or productive environments will cause rapid filter clogging (Robson et al, 2016). Filtering water in turbid environments could be considered one of the most widespread, yet undesirable methodological challenge (Cooper et al, 2021;Ip et al, 2021;Robson et al, 2016;Sanches & Schreier, 2020), but may be compensated with the use of larger pore size filters (e.g., 1.2-20 µm, as in this study; Barnes et al, 2020), prefiltration (Takahara et al, 2013), or multiple filter replicates (Hunter et al, 2019). The downside of these options would be the increase in cost and time for field and laboratory processing of additional replicates (Sepulveda et al, 2019).…”
Section: Methods Sensitivity and Efficiencymentioning
confidence: 99%
“…Evidence suggests that the majority of macro-organismal eDNA is efficiently captured by filter pore sizes between 1 and 10 µm (Turner et al, 2014). Additionally, studies in turbid waters have proven that target species eDNA can be effectively captured using 20 µm filter pore sizes (Cooper et al, 2021;Robson et al, 2016). Therefore, we tested filter pore sizes ranging from 0.45 to 20 µm.…”
Section: Particle Size Fractionationmentioning
confidence: 99%
See 1 more Smart Citation